Assessing the potential clinical impact of reciprocal drug approval legislation on access to novel therapeutics in the USA: a cohort study. Issue 2 (8th February 2017) - Larochelle, Matthieu; Downing, Nicholas S; Ross, Joseph S; David, Frank S
Abstract : Objective: To quantify the potential effect of reciprocal approval legislation on access to clinically impactful therapeutics in the USA. Design: A cohort study. Setting: New therapeutics approved by the Food and Drug Administration (FDA), European Medicines Agency (EMA) and/or Health Canada between 2000 and 2010. Main outcome measures: Characteristics of new therapeutics approved by the EMA and/or Health Canada before the FDA, including mechanistic novelty, likely clinical impact, size of the affected population and FDA review outcome. Results: From 2001 to 2010, 282 drugs were approved in the USA, Europe or Canada, including 172 (61%) first approved in the USA, 24 (9%) never approved in the USA, and 86 (30%) approved in the USA after Europe and/or Canada. Of the 110 new drugs approved in Europe and/or Canada before the USA, 37 (34%) had a novel mechanisms of action compared with drugs already approved by the FDA, but only 10 (9%) were for conditions lacking alternate available therapies in the USA at the time of ex-US approval—of which the majority (9/10; 90%) were indicated for rare diseases. 12 of the 37 agents with novel mechanisms of action approved first in Europe and/or Canada (32%) had their initial FDA submissions rejected for safety reasons—including 2 drugs that were ultimately withdrawn from the market in Europe due to safety concerns. Conclusions: If enacted, reciprocal approval legislation would most likely benefit only a small number of US patients receiving treatment for rare diseases, and the benefit may be somewhat mitigated by an increased exposure to harms.